Instructor's Manual to Accompany Comprehensive perinatal and pediatric respiratory care - Kent B. Whitaker (Delmar Thomson Learning, 2001)
This updated textbook offers a detailed discussion of respiratory care for the newborn and child. It begins with a comprehensive presentation of fetal development of the cardiopulmonary system. Subsequent units cover respiratory care of neonatal and pediatric patients, as well as causes and care of respiratory illnesses. A section devoted to ventilation and oxygenation includes information on new equipment. Important topics such as the care of parents and home care, as well as ten clinical case studies, supplement the main text